EVALUASI PENERAPAN ASAS KEPASTIAN HUKUM DALAM PROSES SERTIFIKASI TANAH OLEH KANTOR PERTANAHAN KABUPATEN BUOL - Ahmad Morad; Alhamid Baharudin; Satria Satria (At-Tanwir Law Review, 2025)
This study aims to evaluate the implementation of the principle of legal certainty in the land certification process carried out by the Land Office of Buol Regency. The principle of legal certainty is a fundamental concept in a rule-of-law state that guarantees land rights in a fair, equitable, and transparent manner. The method used is normative legal research with statutory and conceptual approaches. Data were obtained through a literature review of laws and regulations as well as relevant legal literature. The research findings indicate that although the regulations regarding land certification are already available in a complete and clear form, their implementation at the local level still encounters various obstacles. These include inconsistencies in procedural application, lack of legal understanding among the public, weak protection for vulnerable groups, and the suboptimal state of land administration systems. Therefore, a comprehensive reform of land policies, capacity-building for government apparatus, and a participatory approach that ensures service inclusiveness are urgently needed. This evaluation is expected to contribute to the development of a more just land certification system that upholds legal certainty for all citizens.